Pengaruh Manajemen Risiko terhadap Kinerja Karyawan Melalui Kepuasan Kerja sebagai Variabel Intervening pada PT. Japfa Comfeed Indonesia Tbk Unit Pujungan - Natalia, Ni Putu Riska; Widya Goca, I Gusti Putu Agung; Dwijayanthi, A.A Istri Agung Ovy; Eka Idayanti, I Dewa Agung Ayu (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Companies or organizations need to pay attention to risk management and job satisfaction in improving employee performance. Good risk management and high job satisfaction will result in good performance. There were several problems found related to risk management and job satisfaction in an effort to improve employee performance at PT. Japfa Comfeed Indonesia Tbk Unit Pujungan. This study aims to identify the influence of risk management on employee performance, the influence of risk management on job satisfaction, the influence of job satisfaction on employee performance, and the role of job satisfaction in mediating the influence of risk management on employee performance, with a focus on PT. Japfa Comfeed Indonesia Tbk Unit Pujungan. The research method uses quantitative data with Structural Equation Modeling (SEM) analysis with the Partial Least Square (PLS) approach. This study uses a saturated sample method where the entire population is used as a sample, namely 62 employees. The data were analyzed using Smart PLS, including three stages: outer model analysis, inner model analysis, and hypothesis testing. This study demonstrates that risk management at PT. Japfa Comfeed Indonesia Tbk Unit Pujungan positively influences employee performance and their job satisfaction. Additionally, job satisfaction also contributes positively to employee performance as a partial mediator. Keywords : Employee Performance, Job Satisfaction, Risk Management.